The Impact of Nurse Staffing Levels on Adverse Events, Morbidity, Mortality, and Healthcare Costs - Alrasheedi, Tahani Khatam D, Alanezi, Raim Hussain S, Naimah Fehaid Nasser Alrasheedi, Nawaf Nasar S Alrasheedi, Alrasheedi, Aminah Mansor N, Alshammari Dalal Awwad D (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Nurse staffing levels are a critical factor in healthcare settings, impacting the quality of nursing care and patient outcomes. Objectives: This study aims to assess the impact of nurse staffing on adverse events, morbidity, mortality, and healthcare costs. Methods: Data from two databases were utilized, including 232 acute care hospitals and 124,204 patients across 20 surgical diagnosis-related groups. Adverse events considered were patient fall/injury, pressure ulcer, adverse drug event, pneumonia, urinary tract infection, wound infection, and sepsis. Multilevel analysis was conducted to analyze the effects of nurse staffing, alongside patient and hospital characteristics, on patient outcomes. Results: The study revealed significant associations between nurse staffing levels and adverse events. An increase of 1 hour worked by registered nurses (RNs) per patient day correlated with an 8.9% decrease in pneumonia odds. A 10% increase in RN Proportion was linked to a 9.5% decrease in pneumonia odds. However, higher nursing hours per patient day were associated with a higher likelihood of pressure ulcers. Adverse events were also linked to extended length of stay and increased medical costs. Patients with pneumonia, wound infection, or sepsis had elevated mortality risks during hospitalization. Conclusion: Adverse events occur during hospitalization, necessitating care systems to mitigate their impact. Adequate nurse staffing is crucial in addressing these challenges.